Turkey and Western intelligence cooperation, 1945-1960 - Bezci, Egemen B. (2017)
This thesis examines secret intelligence cooperation between three asymmetric partners – specifically the UK, US and Turkey – from the end of the Second World War until Turkey’s first military coup d'état on 27 May 1960. The thesis shows that our understanding of the Cold War as a binary rivalry between the two blocs is too simple an approach and obscures important characteristics of intelligence cooperation among allies. To reveal a more comprehensive analysis of intelligence cooperation, this thesis develops our understanding of it more broadly, by developing a model called ‘intelligence diplomacy’. This model explores a vital, if little understood, aspect of contemporary international relations given the prevalence of transnational threats today. Intelligence diplomacy involves negotiations and the exploitation of different aspects of joint intelligence activities, synchronized between diplomats and specialized intelligence officers. While such efforts often result in overlap between diplomats and intelligence liaison efforts, there is strong evidence that the acts of intelligence services vary from the instructions of their foreign ministries. The thesis also shows that a pragmatic approach offers states new opportunities to protect national interests, by conducting intelligence diplomacy to influence crucial areas such as nuclear weapons and to exploit cooperation in support of their own strategic imperatives. By doing so this thesis not only reveals previously-unexplored origins of secret intelligence cooperation between Turkey and the West, but also contributes to wider academic debates on the nature of the Cold War by highlighting the potential agency of weaker states in the Western Alliance.